2021
DOI: 10.1093/jpp/rgab006
|View full text |Cite
|
Sign up to set email alerts
|

Augmented cytotoxicity using the physical adsorption of Poloxamer 188 on allicin-loaded gelatin nanoparticles

Abstract: Objectives The aim of this work was to study the effect of the physically adsorbed Poloxamer 188 coating polymer on the cytotoxic activity of allicin-loaded gelatin nanoparticles. Methods The double desolvation method was utilised to prepare the nanoparticles which were characterised for particle size (PS), polydispersity index (PDI) and zeta potential and visualised using transmission electron microscopy. The coating density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…80 Ossama et al prepared allicin-loaded gelatin nanoparticles with poloxamer 188 coating by a double-desolvation method with a particle size of 714 ± 25.21 nm, a PDI of 0.663 ± 0.143, and an EE of 39.32% ± 1.3. 81 The cytotoxicity against HepG2 cells was also enhanced by 3-fold compared with free unformulated allicin. Hashemy et al prepared allicin-loaded chitosan−egg phospholipid nanoparticles (AC-PLCF-NPs) modified with polyethylene glycol and folic acid by a self-assembling method.…”
Section: ■ Delivery Systemsmentioning
confidence: 95%
See 1 more Smart Citation
“…80 Ossama et al prepared allicin-loaded gelatin nanoparticles with poloxamer 188 coating by a double-desolvation method with a particle size of 714 ± 25.21 nm, a PDI of 0.663 ± 0.143, and an EE of 39.32% ± 1.3. 81 The cytotoxicity against HepG2 cells was also enhanced by 3-fold compared with free unformulated allicin. Hashemy et al prepared allicin-loaded chitosan−egg phospholipid nanoparticles (AC-PLCF-NPs) modified with polyethylene glycol and folic acid by a self-assembling method.…”
Section: ■ Delivery Systemsmentioning
confidence: 95%
“…Nanoparticles are nanoscale materials (1–100 nm) with a high surface area and reactivity that can be employed for food delivery to enhance the bioavailability, functionality, quality, and safety of food products by offering high loading capacity and stability, sustained controlled-release properties, and the ability to transport hydrophilic and lipophilic nutrients across cell membranes and biological barriers. , Fan et al prepared allicin-loaded polylactic acid–glycolic acid nanoparticles by a water–oil–water emulsion method with high encapsulation efficiency (EE) and drug loading, as well as a steady controlled-release rate of 75.0 ± 79.20% in an acidic environment and 14.0 ± 67.44% in a neutral environment . Ossama et al prepared allicin-loaded gelatin nanoparticles with poloxamer 188 coating by a double-desolvation method with a particle size of 714 ± 25.21 nm, a PDI of 0.663 ± 0.143, and an EE of 39.32% ± 1.3 . The cytotoxicity against HepG2 cells was also enhanced by 3-fold compared with free unformulated allicin.…”
Section: Delivery Systemsmentioning
confidence: 99%
“…We performed the surface modification of BNPs and CNPs using the classic adsorption method, adjusted from the procedure settled by Ossama et al [ 17 , 28 ]. BNPs or CNPs were resuspended in solutions with increasing equal concentrations of PEG and trehalose (2.5, 6.5, 8.0, and 12.5% v/v and w / v ), respectively, for 12, 24, and 48 h, at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, poloxamer188 (P188) and polysurbate80 are coatings which have been used on NPs for CNS targeted delivery [16]. P188 is an inexpensive and non-ionic surfactant [17], which enhances the internalization of NPs into cells and allows NPs to transfer across the BBB [18]. In this regard, it has been suggested that P188-coated NPs can adsorb apolipoprotein E and interact with LDL receptors on endothelial cells [18].…”
Section: Introductionmentioning
confidence: 99%